Genetic mapping of adult plant stripe rust resistance in the wheat cultivar Kariega - Ramburan, Viresh Premraj (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD (Agric)) -- Stellenbosch University, 2003.